Nilai Budaya Lamaholot dalam Penentuan Harga Jual Kain Tenun Ikat: Studi pada Kelompok Perempuan Penenun Ã¢â‚¬Å“Tene TuenÃ¢â‚¬Â di Nusa Tenggara Timur - Yasmi Nurdin; Gita Elsa Savira; Habib Muhammad Shahib; Irfan Palippui; Muhammad Ridwan Hasanuddin (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2023)
This study aims to reveal the practice of determining the selling price of woven cloth in a women's weaver group called "Tene Tuen". This research was conducted from July to August 2021 through interviews with leaders of the women weaver group. This study used the qualitative method with a descriptive approach as a research method and collected data by using interviews, direct observation, and documentation. This study found that the concept of formulating the selling price set by the (sellers) informants was not only formed by material values but also contained cultural and justice values with a holistic philosophy. In the end, the selling price determined by the tene tuen group seeks to create prosperity and justice for all parties.